A stable Cd-MOF as a dual-responsive luminescent biosensor for the determination of urinary diphenyl phosphate and hippuric acid as biomarkers for human triphenyl phosphate and toluene poisoning. Issue 39 (15th September 2022) - Lei, Mingyuan; Ge, Fayuan; Wu, Tingting; Duan, Xinde; Shi, Zhiqiang; Zheng, Hegen
Abstract : A stable 3D urea-functionalized Cd-MOF has been synthesized, and can be used as a dual-responsive luminescent biosensor for the detection of urinary DPP and HA as biomarkers for human triphenyl phosphate and toluene poisoning. Abstract : Rapid and accurate determination of biomarkers of human poisoning in real urine is of great significance for the assessment of health status. Herein, a luminescent urea-functionalized metal–organic framework (MOF), {[Cd(L)0.5 (bpbix)]· x (solv)} n (1 ) (H4 L = 5, 5′-(((naphthalene-1, 5-diylbis(azanediyl))bis(carbonyl))bis(azanediyl))diisophthalic acid; bpbix = 4, 4′-bis((1 H -imidazol-1-yl)methyl)biphenyl), has been successfully synthesized, and exhibits good stability in aqueous solutions in the normal urinary pH range and real urine. Complex 1 can serve as a dual-responsive luminescent biosensor for the detection of diphenyl phosphate (DPP) and hippuric acid (HA) as biomarkers of flame retardant triphenyl phosphate and toluene poisoning, and shows the advantages of high sensitivity, rapid response, good anti-interference capability, and reversibility. More significantly, complex 1 is successfully applied to the sensitive and accurate detection of DPP and HA in real urine with satisfactory recoveries. This work presents a dual-responsive luminescent MOF-based biosensor for simple, rapid, accurate, and reversible determination of urinary DPP and HA, which has promising application potential for the diagnosis of diseases related to triphenyl phosphate and toluene poisoning.